THE IMAGE OF TOURISM DESTINATIONS OF SAUNG ANGKLUNG UDJO (PHENOMOLOGY STUDIES ON TRAVELERS USING INSTAGRAM ACCOUNTS) - Diani Mustika Prianti (UNIVERSITAS PAKUAN, 2022)
The purpose of this study was to analyze the image of the Saung Angklung Udjo tourist destination and the use of social media Instagram as a reference medium in traveling. Researchers used qualitative methods with a phenomenological approach. The research paradigm used is interpretive, where researchers can see the phenomena that occur and explore personal experiences from the object under study. The results showed that Saung Angklung Udjo is a place to preserve Sundanese culture which is suitable as a cultural tourism destination as well as education. The image of the destination that needs to be paid attention to by the manager of Saung Angklung Udjo, is the potential for culinary tourism, facilities and infrastructure as well as the cleanliness of the tourist attraction area. Tourists use Instagram as a reference medium for sources of information, instructions or guidance and judgments to make decisions. Tourists also use the hashtag, location tag, caption and story features.